The Role of Zakat, Infaq and Sadaqah in the Post-Disaster Economic Recovery of MSMEs: Case Study at Baznas Central Sulawesi Province - Nadia Safitri; Rahmad hakim; Rahmi Amalia (Institut Agama Islam (IAI) Al-Qolam, 2023)
This study aims to determine the role of zakat, infaq and shadaqah Baznas Central Sulawesi Province in the Economic Recovery Efforts for Post-Disaster Business Actors in Palu City. This type of research was a case study approach. Data collection techniques in this study were interviews, documentation, and observation. The data analysis technique used in this research uses the data analysis model of Miles, Huberman, and Saldana. The result of this study indicate that the role of Zakat, Infaq, and Sadaqah Baznas Central Sulawesi Province in the Economic Recovery Efforts for Post-Disaster Business Actors in Palu City was very important. This was indicated by the increase in the income of business actors more than double the previous income with an average nominal percentage of 259% from ten business actor informants. With the increase in the income of these business actors, they can support their families far more adequately than before so that the economic level of the families of business actors increases, this was an indication that the post-disaster economic recovery carried out by the National Amil Zakat Agency of Central Sulawesi Province has been realized with satisfactory results.